2017
DOI: 10.1007/s12325-017-0576-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Therapeutic Utility of Professional Continuous Glucose Monitoring in Type 2 Diabetes Across Various Therapies: A Retrospective Evaluation

Abstract: P-CGM can provide actionable data and motivate patients for diabetes self-care practices, resulting in an improvement in glycemic control over a wide range of baseline therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 21 publications
4
27
1
Order By: Relevance
“…The MAGE in our study was much lower than reported in other study conducted in patients admitted for glycemic control (77.24 vs. 110.3 mg/dL) [17]. In another study (n = 108), CGMS wore for five days showed minimum one hypoglycemia episode motivating and increasing the therapy compliance among the patients [7][8][9][10][11][12][13][14][15]. In this study, we evaluated 24 hour glycemic control by using CGMS device for 6 days, in T2DM patients treated with U-200.…”
Section: Discussioncontrasting
confidence: 58%
“…The MAGE in our study was much lower than reported in other study conducted in patients admitted for glycemic control (77.24 vs. 110.3 mg/dL) [17]. In another study (n = 108), CGMS wore for five days showed minimum one hypoglycemia episode motivating and increasing the therapy compliance among the patients [7][8][9][10][11][12][13][14][15]. In this study, we evaluated 24 hour glycemic control by using CGMS device for 6 days, in T2DM patients treated with U-200.…”
Section: Discussioncontrasting
confidence: 58%
“…Change in the HbA1c was the primary outcome in most of the studies that focused on CGM usage in T2DM. Most studies have demonstrated a reduction in HbA1c with the use of CGM when compared to the controls [7-10,13,16,17]. However, a study done in a university hospital in Japan and published in 2016 demonstrated no significant change in HbA1c when compared to control [11].…”
Section: Discussionmentioning
confidence: 99%
“…The CGMS could also be a useful method to detect postprandial hyperglycaemia and to improve therapeutics management in patients with T2DM. [ 303 335 336 337 ]…”
Section: Mplementationmentioning
confidence: 99%
“…P-CGM motivated the patients for diabetes self-care practices, resulting in an improvement in glycaemic control over a wide range of baseline therapies. [ 336 ]…”
Section: R Ationale and E Videncementioning
confidence: 99%